1995
DOI: 10.1557/jmr.1995.1301
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of tetragonal distortion in the PbTiO3–BiFeO3 system by high-temperature x-ray diffraction

Abstract: Compositions in the (Pb1−xBix (Ti1−xFex)O3 solid solution system for x ⋚ 0.7 show unusually large tetragonal distortion. High-temperature x-ray diffraction was used to study the tetragonal distortion as a function of temperature (25–700 °C) for compositions (x = 0–0.7) using powders prepared by solid-state reaction in the above system. Large changes in the lattice parameters were observed over a narrow temperature range near Curie temperature (TC) for compositions near the morphotropic phase boundary (MPB) (x … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(106 citation statements)
references
References 8 publications
7
98
1
Order By: Relevance
“…An increase in temperature from room temperature to 100 C, for example, causes the c/a ratio to decrease by 10% from approximately 1.10 to approximately 1.09 for the undoped material. Similar results have been reported by Sunder et al 43 and Chen et al 44 It is apparent from Fig. 2 that increasing temperature decreases the tetragonality over the whole compositional range investigated.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…An increase in temperature from room temperature to 100 C, for example, causes the c/a ratio to decrease by 10% from approximately 1.10 to approximately 1.09 for the undoped material. Similar results have been reported by Sunder et al 43 and Chen et al 44 It is apparent from Fig. 2 that increasing temperature decreases the tetragonality over the whole compositional range investigated.…”
Section: Resultssupporting
confidence: 90%
“…2 and also reported elsewhere. 43,44 This would lead to a decrease in achievable strain from domain switching, however, less tetragonal distortion also means lower internal stresses, which should, in principle, allow for more domain switching and thus more strain. The results shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the preferential orientation direction and misfit strain on the deposited unit cells, the known lattice parameters of bulk 0.6BiFeO 3 -0.4PbTiO 3 at room temperature and 565 °C (the deposition temperature) must both be considered to understand the possible orientation development and lattice matching to the substrate. The interatomic spacings describe closely matching lattice parameters between platinum (100) (a = 3.94 Å) and the 0.6BiFeO 3 -0.4PbTiO 3 (001) (a = 3.96 Å) and (100) (a = 3.96 Å, c = 4.06 Å) at the deposition temperature [8,21]. In addition the (001) plane is square which may also increase the likelihood of hetroepitaxial match to the cubic structure of the platinum substrate.…”
Section: 6bifeo 3 -04pbtio 3 Film Structurementioning
confidence: 64%
“…7) and is of special interest due to its multiferroic nature and exceptionally high tetragonality (c/a ratio) of approximately 1.17. For these reasons it is a promising material for ferroelectric applications that require high levels of polarization and temperature stability as well as multiferroic properties [6][7][8][9].…”
mentioning
confidence: 99%
“…Among them PbTiO 3 substitution imparts unique features: (i) inducing Morphotropic phase boundary (MPB) consisting of tetragonal and rhombohedral ferroelectric phase, (ii) high Curie point, and (iii) extremely large tetragonality [2][3][4][5]. However, so far there is no unanimity among the various research groups about the compositional range for the MPB state [2][3][4][5][6][7][8][9]. In this work we have resolved this issue by undertaking a systematic sintering temperature-time study on the reported MPB compositions of (1-x) BiFeO 3 -(x) PbTiO 3 .…”
Section: Introductionmentioning
confidence: 99%